Spatial and Temporal Variability in the Occurrence and Abundance of European Hake Larvae, Merluccius merluccius, on the Galician Shelf (NE Atlantic) - García-Fernández, Cristina; Suca, Justin J.; Llopiz, Joel K.; Álvarez, Paula; Domínguez-Petit, Rosario; Saborido-Rey, Fran (Frontiers in Marine Science, 2021)
European hake represent one of the most valuable fisheries in the Galician Shelf. We analysed the distribution,abundance and environmental conditions of southern-stock European hake larvae onfrom the Galician shelf are analysed during the two main spawning peaks – winter-spring and summer – based on data from three ichthyoplankton surveys (March 2012, March 2017 and June 2017). A total of 395 larvae in March 2012, 121 in March 2017 and 69 in June 2017 were captured. The northeast section of the study area had the highest presence of European hake larvae in all surveys, close to Estaca de Bares, primarily between the 100 and 200 m isobaths. Generalized additive models indicated that the occurrence of larvae was significantly different between surveys and associated negatively with the temperature, while abundances of larvae were significantly different between sampling years and highest at temperatures around 13.36 ºC and sea surface heights around -0.48 meters. Studies of the distribution of early life stages and its relation with the external conditions are essential to understanding the complex process of recruitment, especially in exploited species and in highly dynamic environments like the Galician Shelf.